Genetic Resistance of Egyptian Chickens to Infectious Bursal Disease and Newcastle Disease - Hassan, M.K.; Afify, M.A.; Aly, M.M. (Springer, 2004)
Genetic resistance of native Egyptian breeds to very virulent infectious bursal disease virus (vvIBDV) and Newcastle disease virus (NDV) was investigated in two experiments. In the first experiment, birds from four breeds (Gimmizah, Sina, Dandrawi and Mandarah) were challenged with vvIBDV. The Mandarah chickens had the lowest mortalities (10%) compared to the Gimmizah, Sina and Dandrawi chickens (55%, 35% and 55%, respectively). Antibody response, lymphocyte response to mitogen, and bursal lesions did not clearly correlate with the mortality rates. In the second experiment, the four chicken breeds were challenged with virulent NDV. The Mandarah chickens re-emerged as a resistant breed (20% mortality), while the Sina, Dandrawi and Gimmizah breeds were highly susceptible (85%, 100% and 100% mortality, respectively). Further studies on the resistance mechanism are warranted.